Assessment of inhibition of porcine hepatic cytochrome P450 enzymes by 48 commercial drugs. (May 2016) - Hu, Steven X.; Mazur, Chase A.; Feenstra, Kenneth L.; Lorenz, Julie K.; Merritt, Dawn A.
Highlights: The inhibition of porcine CYP450 by 48 commercial porcine drugs has been assessed. Seventeen drugs inhibit at least one of six porcine CYP450 in vitro . Three drugs show high inhibition potential at their commercial use. Abstract: Drug interactions due to inhibition of hepatic cytochrome P450 (CYP450) enzymes are not well understood in veterinary medicine. Forty-eight commercial porcine medicines were selected to evaluate their potential inhibition on porcine hepatic CYP450 enzymes at their commercial doses and administration routes. Those drugs were first assessed through a single point inhibitory assay at 3 µM in porcine liver microsomes for six specific CYP450 metabolisms (phenacetin o-deethylation, coumarin 7-hydroxylation, tolbutamide 4-hydroxylation, bufuralol 1-hydroxylation, chlorozoxazone 6-hydroxylation and midazolam 1'-hydroxylation). When the inhibition was > 10% in the single point inhibitory assay, IC50 values (inhibitory concentrations that decrease biotransformation of selected substrate by 50%) were determined. Overall, 17 drugs showed in vitro inhibition on one or more porcine hepatic CYP450 metabolisms with different IC50 values. The potential in vivo porcine hepatic CYP450 inhibition by those drugs was assessed by combining the in vitro data and in vivo Cmax (maximum plasma concentrations from pharmacokinetic studies of the porcine medicines at their commercial doses and administration routes). Three drugs showed high potential inhibition to one or two porcine hepatic CYP450 isoforms at their commercial doses and administration routes, while seven drugs had medium risk and seven had low risk of such in vivo inhibition. These data are useful to prevent potential drug interactions in veterinary medical practice.